2020
DOI: 10.21203/rs.3.rs-18973/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

USP46 inhibits cell proliferation in lung cancer through PHLPP1/AKT pathway

Abstract: Background: USP46 has been shown to function as tumor suppressor in colon cancer and renal cell carcinoma. However, its specific role in other cancers remains unknown. This study was aimed to investigate the role of USP46 in lung cancer tumorigenesis, and to identify the underlying mechanism. Methods: Quantitative Real Time-Polymerase Chain Reaction (qRT-PCR) and Western Blotting (WB) were used to measure the expression levels of USP46 and PHLPP1 in lung cancer tissue and adjacent normal tissue from lung cance… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In colorectal cancer, renal cell carcinoma, and lung cancer, USP46 has been confirmed to be abnormally down‐regulated. As a tumor suppressor gene, it can antagonize the activity of AKT by deubiquitinating the PH domain leucine‐rich repeat protein phosphatase 1 (PHLPP1), thereby inhibiting the proliferation of cancer cells (Gui et al, 2019; Li et al, 2013; Wang et al, 2020). In esophageal squamous cell carcinoma, Tian et al confirmed the over‐expression of USP46 by analyzing clinical samples, and in vitro studies confirmed that USP46 enhances the migration and invasion of esophageal squamous cell carcinoma cells by mediating the EMT process (Tian et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal cancer, renal cell carcinoma, and lung cancer, USP46 has been confirmed to be abnormally down‐regulated. As a tumor suppressor gene, it can antagonize the activity of AKT by deubiquitinating the PH domain leucine‐rich repeat protein phosphatase 1 (PHLPP1), thereby inhibiting the proliferation of cancer cells (Gui et al, 2019; Li et al, 2013; Wang et al, 2020). In esophageal squamous cell carcinoma, Tian et al confirmed the over‐expression of USP46 by analyzing clinical samples, and in vitro studies confirmed that USP46 enhances the migration and invasion of esophageal squamous cell carcinoma cells by mediating the EMT process (Tian et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…USP46 stablization of PHLPP reduced AKT activity and led to suppressed tumor growth of colon cancer cells (Li et al, 2013, Wen et al, 2013). USP46 also negatively regulated PHLPP/AKT signaling axis and suppressed cancer cell function in renal cell carcinoma and lung cancer (Gui et al, 2019, Wang et al, 2020). Oppositely, USP46 was shown to participate in high‐risk human papilloma viruses (HPVs) replication (Lehoux et al, 2014).…”
Section: Discussionmentioning
confidence: 99%